Case report: Bone marrow metastasis and bone marrow necrosis occurring 11 years after ductal carcinoma in situ of the breast - Zhang, Shuting; Du, Zhonghai; Wu, Jun; Zhang, Xiaoli; Dong, Wei (Frontiers in Oncology, 2024)
Ductal carcinoma in situ (DCIS), a noninvasive breast cancer, rarely metastasises to distant locations. When the initial lesion is stable, bone marrow metastasis (BMM) and bone marrow necrosis (BMN) are even less common. Here, we report the case of a 47-year-old female patient who underwent localized surgery and radiotherapy for right-sided DCIS. The patient also had a mutation in the breast cancer susceptibility gene 1 (BRCA1, OMIM: 113705) and tested positive for the progesterone and estrogen receptors. After 11 years of disease-free survival, the patient developed severe thrombocytopenia, anemia, fever, malaise, generalized multifocal pain, and irregular vaginal bleeding. A nodule was later found in the right axilla, and a postoperative biopsy revealed tumor cells from the breast. After three bone marrow biopsies, Positron Emission Tomography, 18F-fluorodeoxyglucose, positron emission tomography, computed tomography (18F-FDG PET/CT) scans, and other examinations, she was finally diagnosed with breast cancer BMM and BMN (stable primary lesion without bone metastasis). Despite symptomatic supportive treatment, the patient ultimately died rapidly as her condition deteriorated. In this case, we explored the possible mechanisms of BMM in this patient with DCIS by reviewing the literature related to this case and discussing the heterogeneous clinical presentation and pathologic phenotype. The diagnostic and therapeutic course of this case was extremely challenging. This suggests to clinicians that regular checkups and monitoring are necessary, even if the rate of distant metastasis from DCIS is low.